Markets and marketing strategies in settlements in the metropolitan region of Porto Alegre - Rubenich, Indiane Witcel; Oliveira, Daniela (Desenvolvimento e Meio Ambiente, 2025)
This study was carried out in the settlements of the Metropolitan Region of Porto Alegre (RMPA). This region has 17 MST settlements that stand out for their production of fruit and vegetables and agroecological rice. The objectives of the article are to analyze the process of building markets for products from RMPA settlements and identify the types of markets accessed and the characteristics of these markets. The theoretical perspective used for the analysis states that resistance to the dominant food regime and multinational agribusiness corporations involves the construction of markets and alternative food production and consumption networks. Which rescue social, political, and environmental values ​​and which, according to the typification presented by Schneider (2016), ​are present mainly in proximity markets, in territorial markets and, in some cases, in institutional markets. Interviews and questionnaires were carried out with families settled in negotiation processes. It was identified that (a) local and territorial markets predominate, that (b) there is a good diversification of marketing channels used by families; (c) that these channels allow families to have good conditions for negotiating prices and delivery conditions and also (d) the importance of agroecological food production in the construction of markets and in the conditions of autonomy and management of families over markets.